2023
DOI: 10.3389/fvets.2023.1126911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Galla Chinensis tannin supplementation on immune function and liver health in broiler chickens challenged with lipopolysaccharide

Abstract: Herein, Galla Chinensis tannin (GCT) was examined for its influence on preventing lipopolysaccharide (LPS)-induced liver damage in broiler chickens. Approximately 486 one-day-old healthy broilers were randomly allocated to 3 treatment groups (control, LPS, and LPS + GCT). The control and LPS groups were fed a basal diet and the LPS+GCT group was fed the basal diet supplemented with 300 mg/kg GCT. LPS was intraperitoneally injected (1 mg/kg body weight BW) in broilers in the LPS and LPS+GCT groups at 17, 19, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…The growth performance of broilers may also decrease to a certain extent after liver damage ( 47 ). This experiment found that adding 0.3 g/mL of a compound Chinese herbal medicine with JM113 improved the liver index of broilers, indicating that Chinese herbal medicine is beneficial to liver health, which is consistent with previous studies ( 48 ). It is known that the combined use of compound herbs and JM113 promotes the development of the intestinal tract, thereby boosting the absorption of nutrients by the animal organism, which in turn supports the improvement of the organ index of broilers.…”
Section: Discussionsupporting
confidence: 92%
“…The growth performance of broilers may also decrease to a certain extent after liver damage ( 47 ). This experiment found that adding 0.3 g/mL of a compound Chinese herbal medicine with JM113 improved the liver index of broilers, indicating that Chinese herbal medicine is beneficial to liver health, which is consistent with previous studies ( 48 ). It is known that the combined use of compound herbs and JM113 promotes the development of the intestinal tract, thereby boosting the absorption of nutrients by the animal organism, which in turn supports the improvement of the organ index of broilers.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the results reported by Chen et al ( 26 ), suggesting that TA can enhance the immune function and disease resistance of chicks. Previous studies have also reported a protective effect of TA on the liver ( 30 ). The study found that the administration of TA significantly reduced the colonization of S. pullorum and mitigated liver damage ( 31 ).…”
Section: Discussionmentioning
confidence: 80%
“…Undoubtedly, in addition to the immune organ index, the quantity and activity of immunoglobulins are also critical indicators to evaluate the immune function status of birds. As a key active molecule in the body's immune system, immunoglobulins recognize and clear specific antigens and reflect the humoral immune status of animals ( Yuan et al, 2023 ). In contrast, SIgA is secreted by plasma mother cells and is a major effector in the intestinal immune response system ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%